Game-Based Self-Management: Addressing Inattention during Independent Reading and Written Response. Issue 1 (2nd January 2020) - Harrison, Judith R.; Kwong, Courtney; Evans, Steven W.; Peltier, Corey; Mathews, Leslie; Chatman, Tasia
Abstract: Self-management is a strategy with emerging evidence of effectiveness that has been utilized to address impairment associated with attention deficit hyperactivity disorder (ADHD); however, few studies have been conducted with students with ADHD. The results of the minimal research available suggests that self-management with youth with ADHD is less robust than with students without ADHD. Gamification of self-management tools has the potential to increase positive outcomes with young adolescents with ADHD. The present study utilized a withdrawal design (ABAB) with four 6 th and 7 th grade students with ADHD to evaluate the effectiveness of a game-based self-management application on task engagement, accuracy, and completion in reading. Results indicated a functional relationship between game-based self-management and task engagement, accuracy, and completion with moderate to large effects overall (Tau-U, NAP, BC-SMD). Implications are discussed.